Optogenetic control of mitochondrial aggregation and function - Zhang, Luhao; Liu, Xuechun; Zhu, Min; Yao, Yuanfa; Liu, Zhichao; Zhang, Xianming; Deng, Xin; Wang, Yi; Duan, Liting; Guo, Xiaogang; Fu, Junfen; Xu, Yingke (Frontiers in Bioengineering and Biotechnology, 2025)
The balance of mitochondrial fission and fusion plays an important role in maintaining the stability of cellular homeostasis. Abnormal mitochondrial fission and fragmentation have been shown to be associated with oxidative stress, which causes a variety of human diseases from neurodegeneration disease to cancer. Therefore, the induction of mitochondrial aggregation and fusion may provide an alternative approach to alleviate these conditions. Here, an optogenetic-based mitochondrial aggregation system (Opto-MitoA) developed, which is based on the CRY2clust/CIBN light-sensitive module. Upon blue light illumination, CRY2clust relocates from the cytosol to mitochondria where it induces mitochondrial aggregation by CRY2clust homo-oligomerization and CRY2clust-CIBN hetero-dimerization. Our functional experiments demonstrate that Opto-MitoA-induced mitochondrial aggregation potently alleviates niclosamide-caused cell dysfunction in ATP production. This study establishes a novel optogenetic-based strategy to regulate mitochondrial dynamics in cells, which may provide a potential therapy for treating mitochondrial-related diseases.